Foresight in the EU Forestry Sector - Valentin Strakhov (Foresight and STI Governance)
The importance of forests as a strategic resource and intangible assets is growing. So the forest sector has become a subject of numerous Foresight studies of different level and orientation. The European approach is considered as most productive so it is analyzed in the given paper. The basic instruments of strategic planning, first of all technology platforms and strategic studies implemented in the forest sector on their basis are discussed. A short review of Foresight practices of individual countries is presented. The general conclusion: reforms in the Russian forestry would be successful only if qualitative structural changes will take place. But related steps should be undertaken only on the base of shared future vision for all stakeholders. Results of Foresight studies at different level will allow to determine required innovation changes and to build roadmaps for development of different subsections of Russian forestry.